2020
DOI: 10.1136/bmjgast-2019-000351
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbidities on anti-TNFα response and relapse in patients with inflammatory bowel disease: the VERNE study

Abstract: ObjectiveTo evaluate the impact of comorbidities and extraintestinal manifestations of inflammatory bowel disease on the response of patients with inflammatory bowel disease to antitumour necrosis factor alpha (anti-TNFα) therapy.DesignData from 310 patients (194 with Crohn’s disease and 116 with ulcerative colitis) treated consecutively with the first anti-TNFα in 24 Spanish hospitals were retrospectively analysed. Univariate and multivariate logistic regression analyses were performed to assess the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…A recently published study showed that the presence of the comorbidities chronic obstructive pulmonary disease as well as extra-intestinal hepato-pancreato-biliary conditions were associated with primary non-response and myocardial infarction and skin disease were significantly associated with loss of response to anti-TNF treatment ( 52 ). Further studies will have to investigate these findings.…”
Section: Patient and Disease Related Predictors To Anti-tnf Therapymentioning
confidence: 99%
“…A recently published study showed that the presence of the comorbidities chronic obstructive pulmonary disease as well as extra-intestinal hepato-pancreato-biliary conditions were associated with primary non-response and myocardial infarction and skin disease were significantly associated with loss of response to anti-TNF treatment ( 52 ). Further studies will have to investigate these findings.…”
Section: Patient and Disease Related Predictors To Anti-tnf Therapymentioning
confidence: 99%
“…In any case, in our study, ADA results in the UC cohort should be interpreted cautiously due to the limited number of patients included in this subgroup [20] . These results are somewhat in accordance with those of other published retrospective analyses where UC patients treated with ADA showed higher, albeit not statistically significant, treatment discontinuation rates than those treated with IFX [18 , 43-46] .…”
Section: Article In Pressmentioning
confidence: 91%
“…The study was reviewed and approved by the corresponding ethics committees. The results obtained in the VERNE study on the impact of both comorbidities and extraintestinal manifestations (EIMs) on the response to anti-TNF α therapy have been published elsewhere [20] .…”
Section: Study Populationmentioning
confidence: 99%
“…Our study shows that comorbidities were another important factor affecting the expenses of CD hospitalization. The presence of comorbidities in IBD patients had been proven to adversely affect their health-related quality of life, prolong their hospital stay and increase the risk of postoperative complications (26). Possibly due to common pathogenic pathways with other immune-mediated inflammatory diseases, CD has been associated with multiple chronic comorbidities such as bone diseases, cardiovascular diseases, iron-deficiency anemia, pain, psychological disorders and respiratory illness.…”
Section: P-value Adj P-valuementioning
confidence: 99%